A Comparative Analysis of the Peritextual Features of the English-Urdu Translated Versions of ‘Salome’: Utilizing the Poly-Systemic Approach - Naseer Ahmad; Tayyaba Zainab (English Lecturers and Teachers Association (ELTA), 2024)
This study employed poly-systemic approach to Urdu-English translated version of the seminal text “Salome” where the researcher tried to find out the peri-textual feature in both the versions while comparing them. Furthermore. This study aimed to explore the cultural influence on language spoken within a specific area. The method used in this study was descriptive-qualitative in nature. It used two different versions of the same text. The textual analysis established, while taking into consideration the initial, preliminary and operational norms (taken from the peritexts), that majority of the translators and translation critics aligned with the target-oriented or acceptability paradigm and reflected as well as conformed to the secondary position of translation in literary (poly) systems of Pakistan. However, the study found that found that people usually share their culture with other while using language. Moreover, the two versions have specific terminologies representing same ideologies or concepts but they have different sentence constructions. The study was significant as it not only offers contextual information about the process of translation provided by the translators and critics but also because of being first of its kind in Pakistan. Keywords: Salome; compative translation analysis; poly-systemic approach; peri-textual feature